2021
DOI: 10.3390/v13101949
|View full text |Cite
|
Sign up to set email alerts
|

The Holin-Endolysin Lysis System of the OP2-Like Phage X2 Infecting Xanthomonas oryzae pv. oryzae

Abstract: Most endolysins of dsDNA phages are exported by a holin-dependent mechanism, while in some cases endolysins are exported via a holin-independent mechanism. However, it is still unclear whether the same endolysins can be exported by both holin-dependent and holin-independent mechanisms. This study investigated the lysis system of OP2-like phage X2 infecting Xanthomonas oryzae pv. oryzae, causing devastating bacterial leaf blight disease in rice. Based on bioinformatics and protein biochemistry methods, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The co-existence of holin and endopeptidase had an obvious bactericidal effect on E. coli than that of holin or endopeptidase alone, which indicated that holin might help the release of endopeptidase. Similar phenomena have been reported in other phages, including the lytic systems of bacteriophage phiSASD1 and OP2-Like Phage X2 ( Nl et al, 2020 ; Wu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 81%
“…The co-existence of holin and endopeptidase had an obvious bactericidal effect on E. coli than that of holin or endopeptidase alone, which indicated that holin might help the release of endopeptidase. Similar phenomena have been reported in other phages, including the lytic systems of bacteriophage phiSASD1 and OP2-Like Phage X2 ( Nl et al, 2020 ; Wu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 81%
“…In most of the previously reported Xoophages, members of holins and endolysins have been found involved in the lysis function. Holins create holes or pores in the lipid bilayer membrane of the host bacterium, thus allowing other enzymes of the lysis module to pass through the holes, whereas Rz spanin like lysis protein assists the lysozyme to enter the outer membrane from the inner membrane while one among the endolysins is peptidoglycan endopeptidase escapes through the holes and cleaves the peptide moiety, the structural portion of the bacterial cell wall ( Wu et al, 2021 ). All these enzymatic activities lead to the difference in osmotic pressure between the bacterial cell and its surrounding environment, thus finally resulting in complete cell lysis and release of progeny phage particles.…”
Section: Discussionmentioning
confidence: 99%
“…This is also evident from the morphology of the plaques ( Figure 1 ) and one-step growth ( Figure 2 ). Most tailed phages make use of the archetypical holin-endolysis system to induce the lysis of the host cell and the release of virions [ 36 , 37 , 38 ]. Holin-like class I and class II genes and lysin were identified, thus indicating lytic activity.…”
Section: Discussionmentioning
confidence: 99%